1975
DOI: 10.1136/hrt.37.6.656
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stenosis, angina, and coronary artery disease. Interrelations.

Abstract: Subjects and methodsCardiac catheterization laboratory records were reviewed to identify all patients who had undergone both diagnostic catheterization for evaluation of aortic stenosis and coronary arteriography from the date it became routine policy in our hospitals to perform the latter procedure on all cases of left ventricular outflow obstruction before surgery. Since we were interested in examining only those patients with unequivocally severe aortic stenosis who were in an age range which could make con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0
1

Year Published

1978
1978
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 6 publications
2
16
0
1
Order By: Relevance
“…Among patients with AS, the prevalence of CAD is 40% to 50% in those with typical angina, an average 25% in those with atypical chest pain, and an average 20% in those without chest pain. [1003][1004][1005][1006][1007][1008][1009][1010] Even in patients less than 40 years old with no chest pain and no coronary risk factors, the prevalence of CAD is 0% to 5%. 998,1005,1011 In elderly patients (greater than 70 years old), angina is a strong determinant of CAD (sensitivity 78%, specificity 82%).…”
Section: Probability Of Coronary Artery Disease In Patients With Valvmentioning
confidence: 99%
“…Among patients with AS, the prevalence of CAD is 40% to 50% in those with typical angina, an average 25% in those with atypical chest pain, and an average 20% in those without chest pain. [1003][1004][1005][1006][1007][1008][1009][1010] Even in patients less than 40 years old with no chest pain and no coronary risk factors, the prevalence of CAD is 0% to 5%. 998,1005,1011 In elderly patients (greater than 70 years old), angina is a strong determinant of CAD (sensitivity 78%, specificity 82%).…”
Section: Probability Of Coronary Artery Disease In Patients With Valvmentioning
confidence: 99%
“…In nations with a higher prevalence of CAD it may be reasonable to perform coronary angiography routinely from an earlier age. Indeed it has been recommended that patients with valvular heart disease over age 40 years undergo coronary angiography at the time of diagnostic cardiac catheterization (Baxter et al, 1978;Harris et al, 1975;Mandal et al, 1976;Roberts, 1982).…”
mentioning
confidence: 99%
“…It has been suggested that the resultant myocardial ischemia or infarction secondary to severe coronary artery disease leads to a fall in the systolic pressure gradient acros the aortic valve. Nevertheless, severe angina pectoris may occur in the abse nce of coronary artery disease in those who have a rugh degree of obstructive aortic valve disease and a valve area of 0.5 cm 2 or less (4,7,10,13). The c1irucal feature of crescendo angina in our patient led us to believe that significant coronary artery disease was at least partially responsible for generating the symptoms.…”
Section: Oinieal Findings and Coursementioning
confidence: 60%